A new strategy to construct gold nanocluster-based optical probes using luminescence resonance energy transfer. Issue 45 (10th May 2021) - Zhai, Shuyang; Hu, Wei; Fan, Chen; Feng, Wenqi; Liu, Zhihong
Abstract : Monolayer protected gold nanoclusters were applied as a pH sensitive luminescent NIR probe based on the LRET mechanism in living cells. Abstract : Monolayer-protected metal nanoclusters (MPCs) are emerging as intriguing luminescent materials, but the construction of MPC-based optical probes is still scarce because of both the limited photoluminescence efficiency of MPCs and the lack of recognition mechanism. We herein propose a luminescence resonance energy transfer-based strategy to circumvent these problems.